Analysis of Performance Measurement of Tobacco Excise Revenue Using Value for Money Method: (Case Study of Customs and Excise Supervision and Service Office Type Madya Excise Kediri) - Sadiyah, Halimatus; Fauziyah; Srikalimah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
In 2020-2023 many sectors, especially the economy, were affected during and after the COVID-19 pandemic in Indonesia. The Ministry of Finance continued to increase excise tax rates on tobacco products from 2020 to 2024. This policy is expected to increase state revenue and reduce underage cigarette consumption. If the excise tax on tobacco products increases, the selling price will increase. This will lead to the spread of illegal cigarettes, which will interfere with state revenue. In this study, the value for money method is used to evaluate the performance of tobacco excise revenue using economic, effective, and efficient indicators. This research uses a quantitative description with a period of years. 2020 - 2023. The results of this study analyzed in terms of economics from 2020 to 2023 fluctuated with an average value of 96,97%. The results of the analysis in terms of efficiency from 2020 to 2023 experienced consistency with an average value of 100,00%. The results of the analysis in terms of effectiveness from 2020 to 2023 show that during this period, the performance value remained stable in a very close range with an average value of 100,10%.